HUBUNGAN ASUPAN LEMAK DAN ZINK DENGAN KEBUGARAN JASMANI PADA REMAJA DI SMK WIDYA PRAJA UNGARAN - Azimah, Uly; Mulyasari, Indri Mulyasari; Purbowati (JURNAL GIZI DAN KESEHATAN, 2018)
Background :Physical fitnessis expected to have a dole scence making itable to work effectively and efficiently, easily absorba lesson,not susceptible to the disease and can perform optimally both in the field of education as well as in the field of sport. One of the nutrients that can affect the level of physical fitness that is fat in take and zink. Purpose :This research aims to know the correlation between of fat in take and physical fitness with zink in a dolescence. Methods: The design ofthis researchis a cross-sectional students witha method that is122. Fat intake and zink in size with the method of total sampling method of semiquantitativeFFQ consumptions urveys. Physical fitnessis measured by the method of Multistage Fitness Test(VO2max), analysis using the spearman rank correlation between test(α=0.05). Results: The mean fat in take on adole scence that is 72.2%±0,85%, zinc intake mean 7.64%, ±2,89% and physical fitness 26.59%± 6,31%.Bivariat analysis shows that there is no correlation between fat intake with physical fitness (p=0.493)where asatthe in take bivariate analysis using zink showed no correlation with physical fitness zini intake (p =0,033). Conclussion :There is no correlation between is no of fat intake with physical fitness in youth,and there is correlation between of physical fitness with zinc intake in adolescence Abstrak : Latar Belakang: Remaja diharapkan memiliki kebugaran jasmani sehingga mampu bekerja secara efektif dan efisien, mudah menyerap pelajaran, tidak mudah terserang penyakit dan dapat berprestasi secara optimal baik dibidang pendidikan maupun dibidang olahraga. Salah satu zat gizi yang dapat mempengaruhi tingkat kebugaran jasmani yaitu asupan lemak dan zink. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan asupan lemak dan zink dengan kebugaran jasmani pada remaja. Metode: Rancangan penelitian ini adalah cross-sectional dengan metode total sampling yaitu 122 siswa. Data asupan lemak dan zink di ukur dengan metode survei konsumsi FFQ semi kuantitatif. Kebugaran jasmani diukur dengan metode Multistage Fitnes Test yaitu VO2max. Analisis data menggunakan uji korelasi Spearman Rank (α = 0,05). Hasil: Rerata asupan lemak pada remaja yaitu 72,2%± 0,85%, rerata asupan zink yaitu 7,64% ± 2,89%dan rerata kebugaran jasmani 26,59% ± 6,31%. Tidak ada hubungan antara asupan lemak dengan kebugaran jasmani (p=0,493). Ada hubungan asupan zink dengan kebugaranjasmani (p=0,033). Simpulan:Tidak ada hubungan asupan lemak dengan kebugaran jasmani pada remaja, dan ada hubungan asupan zink dengan kebugaran jasmani pada remaja.